The Influence of the Qris Payment System on Business Performance Denpasar City MSMEs - Rettobjaan, Vitalia Fina Carla; Widnyani, Ni Made; Richadinata, Kadek Riyan Putra (Global Health Science Group, 2023)
This research was conducted in the context of technological developments and the important role of Financial Technology (Fintech) in encouraging financial inclusion and business growth in the Micro, Small and Medium Enterprises (MSME) sector. The background of this research is the era of industrial revolution 4.0 which has changed the global economic landscape with rapid changes in the fields of technology and information. The aim of this research is to investigate the effect of using the QRIS (Quick Response Code Indonesia Standard) payment system on the financial and non-financial business performance of MSME players. The research method used involved 75 respondents who were MSME actors. Data on respondent characteristics, use of QRIS, and business performance were evaluated. The research results show that the use of QRIS has a significant influence on the financial and non-financial business performance of MSME players. More than 80% of respondents who use QRIS well have good financial and non-financial business performance. The positive effects of using QRIS indicate that this technology can increase transaction efficiency, consumer convenience and MSME business growth.